Pemetaan Kualitas Air pada Rumah Pelanggan yang Dilayani PDAM Sleman Unit Nogotirto Tahun 2023 - Simatupang, Endah Wulanjani; Santjoko, Herman; Amalia, Rizki; Suwerda, Bambang (Jurnal Kesehatan Lingkungan Mandiri, 2024)
Water quality must meet the mandatory parameters listed in the environmental health quality standards, especially in drinking water media. In chemical parameters, the residual chlor content in the homes of PDAM Sleman Nogotirto Unit customers based on distance shows a lower content in the area with the farthest distance from PDAM Sleman Nogotirto Unit. making researchers to conduct mapping using Geographic Information Systems (GIS) to determine the distribution map of water quality in customers' homes to the distance of PDAM Sleman Nogotirto Unit.This research is descriptive analytic with observation survey method and laboratory result analysis. The design used is an ecological study with a variable prospective approach through GIS-based mapping with GIS modeling techniques in the form of overlays and buffers with spatial interpolation analysis. the presence of water quality at a distance can be related. The state of residual chlor at the farthest distance (Banyumeneng) has decreased followed by the results of the IDW and Kriging interpolation techniques showing a difference in color gradation in the farthest area. while pH and temperature are still within the insignificant line with data analysis of overlay, buffer, and interpolation. Based on the results of the interpolation analysis, it can be concluded that the residual chlor water quality that affects the distance is at the farthest distance of 4.1 km in the Banyumeneng Region with a residual chlor concentration of 0 mg / l seen in the color gradation of the region. The results of the influence of water quality on distance can be visualized in the interpolation method of IDW and kriging techniques.